1874 Mo. Laws 43 - (:unkn) unknown (My University, 1874)
An Act to prevent the carrying of concealed weapons § 1: Prohibited concealed carry of any fire-arms, Bowie-knife, dirk, dagger, slung-shot, or other deadly weapon in any church, place of religious worship, school-room, assembly for educational, literary, or social purpose, election precincts on election day, or court-room while court is in session.
Keywords: CARRY - CERTAIN PUBLIC PLACES; CARRY - CONCEALED